BASIC NETWORK PENETRATION TESTING WITH THE NETWORK TOOL NETCAT IN LINUX-BASED OPERATING SYSTEMS: BASIC NETWORK PENETRATION TESTING WITH THE NETWORK TOOL NETCAT IN LINUX-BASED OPERATING SYSTEMS - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this scientific article a basic network penetration testing with the network tool Netcat in Linux-based operating systems is presented.